Legal Protection of Famous Brand Rights (Well-Known Mark) Starbucks (Studi Putusan Mahkamah Agung Nomor 836 K/PDT.SUS-HKI/2022) - Marchelya*, Vanya; Rahaditya, R. (Riwayat: Educational Journal of History and Humanities, 2023)
The case pertaining to the disagreement between Starbucks Company and PT Sumatra Tobacco Trading Company was resolved at the cassation level by Supreme Court Decision Number 836 K/PDT.SUS-HKI/2022, and at the first level by Commercial Court Decision Number 51/Pdt.Sus/Merek/2021 /PN. Where the conflict arose from the complaint filed in class 34 against PT Sumatra Tobacco Company to cancel the use of the "Starbucks" brand. There were significant discrepancies between the first-level ruling and the cassation-level decision. One of the key elements in analyzing a court decision is the judge's consideration. Thus, disagreements and court rulings will be studied in this study. Since 2012, PT Sumatra Tobacco Trading Company has had a brand license and registered the "Starbucks" trademark then, in 2020, the new.